UNIVERSITAS, PASAR DAN EROS PENGETAHUAN - Mikhael Dua (Litbang STFT Widya Sasana Malang, 2009)
The phrase of “the knowledge based economy” has become one of our main questionings in our universities nowdays. With its basic assumption that science can be placed as a commodity that has its own price in the market place, this ideology pushes the concept of the culture of science out of the focus of the university. If before, science played its role as an important clue in the proccess of higher education, now this focus has been turned aside for the sake of money. This background invites us to think more and more about the idea of university. Instead of following the logic of market, this article tries to focus on the eros or the drives to learn as a fundamental nature of university as a community of explorers. The purpose of university is to have the intellectual excellence, to grow in the important truth and to serve the human and the nature.